2020
DOI: 10.1002/hbm.25107
|View full text |Cite
|
Sign up to set email alerts
|

Sense of external agency is sustained by multisensory functional integration in the somatosensory cortex

Abstract: “Sense of agency” (SoA), the feeling of control for events caused by one's own actions, is deceived by visuomotor incongruence. Sensorimotor networks are implicated in SoA, however little evidence exists on brain functionality during agency processing. Concurrently, it has been suggested that the brain's intrinsic resting‐state (rs) activity has a preliminary influence on processing of agency cues. Here, we investigated the relation between performance in an agency attribution task and functional interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…This null result of anodal tDCS might be ascribed to the electrode layout in which the positioning of both stimulant electrode (rTPJ) and return electrode (lOFC) are important for simultaneously upregulating (anodal current) one area and downregulating (cathodal current) the other area. While both the rTPJ and OFC are involved in theory of mind and sense of agency (Piras et al, 2020 ; Sabbagh, 2004 ), inhibition of the lOFC might counteract the exhilarating effect of the rTPJ on RTs. However, inhibiting the rTPJ by cathodal tDCS resulted in shortened RTs to follow harming orders.…”
Section: Discussionmentioning
confidence: 99%
“…This null result of anodal tDCS might be ascribed to the electrode layout in which the positioning of both stimulant electrode (rTPJ) and return electrode (lOFC) are important for simultaneously upregulating (anodal current) one area and downregulating (cathodal current) the other area. While both the rTPJ and OFC are involved in theory of mind and sense of agency (Piras et al, 2020 ; Sabbagh, 2004 ), inhibition of the lOFC might counteract the exhilarating effect of the rTPJ on RTs. However, inhibiting the rTPJ by cathodal tDCS resulted in shortened RTs to follow harming orders.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the various aspects of the embodied self, studies suggested that its neural correlates involve posterior brain regions, particularly the temporoparietal junction and the extrastriate body area (15,16). In a recent resting-state functional connectivity study, Piras et al (17) suggest that the activity of the brain at rest is influencing individual selfattribution by linking somatosensory representations to visual and proprioceptive information (17). Moreover, the embodied self is described to be essential in the foundation of other kinds of selves, which rely on higher levels of brain function (5,18).…”
Section: Seven Forms Of the Self In Dementia Embodied Selfmentioning
confidence: 99%
“…In addition, new insights from neuroimaging studies highlighted the role of resting-state activity in regions responsible for preparing information for visuo-motor integration. Specifically, it has been suggested that the activity of the brain at rest in action-related perceptual and motor circuits needs to interact in order to create a feeling of control over events (17).…”
Section: Agentic Selfmentioning
confidence: 99%
See 1 more Smart Citation